Correlates of disability in depressed older adults with bipolar disorder - Gildengers, Ariel (2013)
Aims To identify clinical factors associated with disability in depressed older adults with bipolar disorder (BPD) receiving lamotrigine. Methods Secondary analysis of a multi-site, 12-week, open-label, uncontrolled study of addon lamotrigine in 57 adults 60 years and older with BD I or II depression. Measures included the Montgomery Asberg Depression Rating Scale (MADRS), Young Mania Rating Scale (YMRS), Cumulative Illness Rating Scale for Geriatrics (CIRS-G), Dementia Rating Scale (DRS), and WHO-Disability Assessment Scale II (WHO-DAS II). Results Medical comorbidiy in this group of elders was substantial, with roughly 60% of subjects having disorders of the vascular, musculoskeletal/integument, and endodrine/metabolic/breast systems. We found significant relationships among mood (MADRS), medical comorbidity (CIRS-G), cognition (DRS), and disability (WHO-DAS II). More severe BPD depression, more medical comorbidity and more impaired cognition were all associated with lower functioning in BPD elders. Conclusions Our findings fit the paradigm shift that has been occurring in BPD, supporting the notion that BPD is not solely an illness of mood but that it affects multiple domains impacting overall functioning.